2008
DOI: 10.1063/1.2912822
|View full text |Cite
|
Sign up to set email alerts
|

Selective organization of solution-processed organic field-effect transistors

Abstract: Semiconductor channels of organic field-effect transistors have been directly self-organized from a solution phase. The alkyl-modified surface was locally patterned by using a phenyl self-assembled monolayer (SAM) for the channels. Drop-cast small organic molecules were selectively crystallized on the phenyl SAM region. The self-organized process allows the simultaneous formation of polycrystalline transistor arrays from the patterned channels. The phenyl SAM under the channel is critical for the improvement o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
89
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(91 citation statements)
references
References 13 publications
2
89
0
Order By: Relevance
“…Thus, the less-ordered structure and greater d -spacing in the C8-BTBT crystal fi lm would decrease the charge transfer integral between co-facially arranged π-conjugated molecules (Figure 3 c), whereas the more ordered structure and compressively strained molecular lattice of the C8-BTBT:PSS fi lm would increase the overall charge transfer integral through strong electronic coupling between the molecules (Figure 3 d). [ 25 ] To evaluate the effect of the structural evolution and the size of the single-crystal domains on the C8-BTBT:PSS fi lm at the millimeter scale, we fabricated OFETs and measured the characteristics of charge-carrier transport in the corresponding fi lms. The bottom-gate and top-contact OFETs ( L = 100 µm and W = 1000 µm, as defi ned by Ag source/drain electrodes) were fabricated on a heavily n-doped silicon/SiO 2 ( t ox = 200 nm) substrate modifi ed with a self-assembled monolayer (SAM), as shown in the schematic in Figure 4 a. Molybdenum trioxide (MoO 3 ) prepared via thermal evaporation was used as a hole injection layer (HIL) to make an energy-level alignment between the Ag source/drain electrodes and organic semiconductors.…”
Section: Communicationmentioning
confidence: 99%
“…Thus, the less-ordered structure and greater d -spacing in the C8-BTBT crystal fi lm would decrease the charge transfer integral between co-facially arranged π-conjugated molecules (Figure 3 c), whereas the more ordered structure and compressively strained molecular lattice of the C8-BTBT:PSS fi lm would increase the overall charge transfer integral through strong electronic coupling between the molecules (Figure 3 d). [ 25 ] To evaluate the effect of the structural evolution and the size of the single-crystal domains on the C8-BTBT:PSS fi lm at the millimeter scale, we fabricated OFETs and measured the characteristics of charge-carrier transport in the corresponding fi lms. The bottom-gate and top-contact OFETs ( L = 100 µm and W = 1000 µm, as defi ned by Ag source/drain electrodes) were fabricated on a heavily n-doped silicon/SiO 2 ( t ox = 200 nm) substrate modifi ed with a self-assembled monolayer (SAM), as shown in the schematic in Figure 4 a. Molybdenum trioxide (MoO 3 ) prepared via thermal evaporation was used as a hole injection layer (HIL) to make an energy-level alignment between the Ag source/drain electrodes and organic semiconductors.…”
Section: Communicationmentioning
confidence: 99%
“…This material system, particularly in the form of thin and ultra-thin films, finds applications in a variety of technologically relevant fields, including catalysis, 1 gas sensors, 2,3 optically switchable coatings, 4,5 high-energy density solid-state microbatteries, 6,7 smart windows technology, 8,9 flexible supercapacitors, 10 thin film transistors (TFTs) 11 and organic electronics. [12][13][14][15][16][17][18][19][20][21][22] Owing to its high work function -up to 6.9 eV [12] and to the layered structure of α-MoO 3 , MoO x is also employed as a 2D material beyond graphene and as efficient hole contact on 2D transition metal dichalcogenides for p-type field effect transistors (p-FETs). [23][24][25] In view of a reliable device performance, the control over the chemical and physical properties of the MoO x system is mandatory.…”
mentioning
confidence: 99%
“…Already several groups reported that mobility of organic single crystals is as high as 20 cm 2 /Vs or even higher, [4][5][6] so that 100 MHz clock frequency can be predicted with micrometer-channel devices assuming a standard charging model. Furthermore, techniques of solution-based crystallization is being developed very recently, [7][8][9] so that even mobility as high as 5 cm 2 /Vs is achieved from solution, [ 10 ] suggesting that low-cost production routes on fl exible panels can serve for mass-producing the platforms of low-price and mediumperformance integrated circuits.…”
Section: Doi: 101002/adma201000480mentioning
confidence: 99%